The Islamic Utopia: The Illusion of Reform in Saudi Arabia By Andrew Hammond (London: Pluto Press, 2012. 240 pages.) (American Journal of Islam and Society, 2014)
This book is an interesting exposition of the reform discourse and reformironies in the desert kingdom of Saudi Arabia ... a country ambivalent in itssense of security and insecurity, content in its presumed “orthodoxy,” uncertainabout where it fits in this world and about its future, and unsure as to whatextent it can continue to linger in its self-imposed cocoon – and yet, by thesame token, how far it can go in opening up to a perceived threatening world.All of this ambivalence, as one senses while reading the book, hinders, obstructs,and consequently undermines King Abdullah’s alleged attempts at reform.In fact, as Hammond points out, many of these reforms have beennothing but “window dressing … driven entirely by the desire to protect theextraordinary powers of the Saudi royal family,” as well as by a felt necessityto appease the Americans (p. 150).Despite the king’s efforts to project the image of himself as a reformist,one “religious reform” (ṣaḥwah) figure describes him as simply being “outof the arena” (p. 137). Reforms, particularly judicial reforms, which Hammonddescribes as Abdullah’s “central plank,” are defined by a Najdi contextas well as in Najdi terms (Najd is the central region of the Arabian Peninsula).The result has been a polity “trapped” within a pre-modern framework and ...